Large-Area Plasmonic Substrate of Silver-Coated Iron Oxide Nanorod Arrays for Plasmon-Enhanced Spectroscopy - Carvalho, Waldemir Moura; Volpati, Diogo [UNESP]; Nunes Carvalho, Vitor A.; Aroca, Ricardo F.; Constantino, Carlos J. L. [UNESP]; Souza, Flavio L. (Wiley-Blackwell, 2013)
One-dimensional iron oxide materials fabricated on conducting glass substrates and their unique properties make these nanostructures promising candidates for a wide range of applications. Herein, vertically oriented -Fe2O3 nanorod arrays synthesized under hydrothermal conditions over a large area are described, as an active platform for surface-enhanced resonance Raman scattering (SERRS) and surface-enhanced fluorescence (SEF). From scanning electron microscopy images the formation of a homogeneous distribution of vertically oriented rods in a large area is confirmed. For activating the localized surface plasmon resonances, which are responsible for SERRS and SEF, a 6 nm layer of Ag is deposited onto the -Fe2O3 nanorod arrays by physical vapor deposition to form Ag islands.
Keywords: fluorescence; iron oxide; nanostructures; Raman spectroscopy; surface plasmon resonance